Analisis Efisiensi Kinerja Keuangan Lazismu Kota Metro Dengan Pendekatan Data Envelopment Analysis (DEA) - Alfin, Alif; Suhada, Bambang (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the level of efficiecny of the finacial performance of zakat, infaq and shadaqah muhammadiyah institutions metro city period 2019-2020, the research design used in this research is quantitative research with an intermediation approach. The population of this study is the amil zakat infaq and shadaqah muhammadiyah institutions in metro city and the research sample is financial statments the amil zakat infaq and shadaqah muhammadiyah institutions in metro city, by using the Data Envelopment Analysis (DEA) and using input variables consisting of total assets, zakat funds receipts, infaq, shadaqah and output variables consisting of operational costs, distribution of zakat funds, infaq and shadaqah. The results of this study show that in 2019-2020 zakat infaq and shadaqah muhammadiyah institutions has an efficiency score of 1,000 which means that in those 2 years the zakat infaq and shadaqah institutions in metro city has had a good performance and runs the management efficienctly, with a score of 1,000 in 2019 and 2020, then there is no inefficency in zakat infaq and shadaqah muhammadiyah institutions in metro city. Keywords: Eficciency, Data Envelopment Analysis (DEA), Intermediation, amil zakat infaq and shadaqah muhammadiyah institutions.